Analisis Putusan Mahkamah Agung Nomor 1699/K/Pid/2025 tentang Tindak Pidana Penipuan Perspektif Hukum Positif dan Hukum Pidana Islam - Muhammad Airlangga Putra (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to analyze the Supreme Court Decision Number 1699/K/Pid/2025 concerning fraud from the perspectives of positive law and Islamic criminal law. The study focuses on the legal considerations of the judges in categorizing the legal relationship between the defendant and the victim as a criminal act of fraud under Article 379a of the Indonesian Criminal Code, despite the existence of civil elements such as debt acknowledgment, partial payment, and installment agreements. This research employs normative juridical methods using statutory, conceptual, and case approaches. The legal materials consist of primary legal sources in the form of court decisions and legislation, as well as secondary legal sources including journals, books, and scientific articles published within the last five years. The findings indicate that the Supreme Court's decision remains debatable because there are doubts regarding the existence of criminal intent from the beginning of the transaction. From the perspective of positive law, the decision potentially contradicts the principles of legal certainty, ultimum remedium, and in dubio pro reo. Meanwhile, in Islamic criminal law, the case contains elements of syubhat due to the ambiguity between fraud and breach of contract, thus punishment should be avoided based on the principle of al-hudud tudra'u bisy-syubuhat. Therefore, settlement through civil mechanisms is considered more reflective of justice and legal benefit than criminal punishment.